Implementación de una aplicación móvil de lenguaje de señas mediante la metodología madamdm, que permita mejorar el proceso de enseñanza-aprendizaje en el área de matemáticas para los niños con discapacidad auditiva de 2do a 4to grado en el Instituto de Educación Especial Cotopaxi a partir del periodo diciembre 2014-diciembre 2015 - Aguilar Calvache, Layan Rubén (2016)
At the Institute of Special Education Cotopaxi located in the Betlemitas neighborhood of Latacunga Canton, we observed that each teacher is manages the way teaching and learning to children with hearing impairment in the area of mathematics. So this thesis was realized in order to facilitate the learning of basic operation of mathematics as tool of help, so that children and teachers can rely on a material of technological support in the education of children inside and outside of classroom....